"Advanced Marriage Technique": Sex as a Perfectible Skill in Mid-twentieth-century American Marriage Manuals. (October 2021) - Lavine, Matthew
While earlier marital advice literature treated sexual intercourse as a matter of conditioned instinct, marriage manuals in the mid-twentieth century portrayed it as a skill, and one that was rarely cultivated adequately. The didactic, quantified, objectively examined and rule-bound approach to sex promulgated by these manuals parallels other ways in which Americans subjected their personal and intimate lives to the tutelage of experts. Anxieties about the stability of marriage and family life were both heightened and salved by the authoritative tone of scientific authority used in these books.